Answer:
[tex]\frac{d}{dx}[f(x)+g(x)+h(x)] = \frac{9\cdot x^{8}}{\sqrt{1-x^{18}}} - 81\cdot x^{80}-2\cdot x[/tex]
Step-by-step explanation:
This derivative consist in the sum of three functions: [tex]f(x) = 81\cdot \sin^{-1} x^{9}[/tex], [tex]g(x) = - x^{81}[/tex] and [tex]h(x) = - x^{2}[/tex]. According to differentiation rules, the derivative of a sum of functions is the same as the sum of the derivatives of each function. That is:
[tex]\frac{d}{dx} [f(x)+g(x) + h(x)] = \frac{d}{dx} [f(x)]+\frac{d}{dx} [g(x)] +\frac{d}{dx} [h(x)][/tex]
Now, each derivative is found by applying the derivative rules when appropriate:
[tex]f(x) = 81\cdot \sin^{-1} x^{9}[/tex] Given
[tex]f'(x) = \frac{9\cdot x^{8}}{\sqrt{1-x^{18}}}[/tex] (Derivative of a arcsine function/Chain rule)
[tex]g(x) = - x^{81}[/tex] Given
[tex]g'(x) = -81\cdot x^{80}[/tex] (Derivative of a power function)
[tex]h(x) = - x^{2}[/tex] Given
[tex]h'(x) = -2\cdot x[/tex] (Derivative of a power function)
[tex]\frac{d}{dx}[f(x)+g(x)+h(x)] = \frac{9\cdot x^{8}}{\sqrt{1-x^{18}}} - 81\cdot x^{80}-2\cdot x[/tex] (Derivative for a sum of functions/Result)